PENDAPATAN PAJAK DARI PBB–P3 - Leader Joy Lumbanraja; Mila Susanti (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
The Directorate General of Taxes was a partner of the government in implementing tax reform to increase tax revenue which would be managed by the government and set forth in the APBN. The purpose of this study was to determine the effect of PBB-P3 on tax revenue at DJP based on secondary data from the 2001-2019 DJPs annual report. The research method used was a confirmative method processed from quantitative data. The data analysis used was descriptive analysis, correlation coefficient, determination coefficient, significance test and simple regression. The results showed that the average increase in PBB-P3 revenue from year to year was 8.57%, while the average increase in tax revenue at DJP was 12.9%. PBB-P3 revenue has a moderate relationship (0.4025) and contributes 16.8% to the tax revenue received by DGT. The significance test shows that Ho was accepted (sig. 0.0977> 0.05) so that PBB-P3 did not have a significant effect on tax revenue at DJP.